2019
DOI: 10.1002/stc.2320
|View full text |Cite
|
Sign up to set email alerts
|

Automatic mapping of cracking patterns on concrete surfaces with biological stains using hyper-spectral images processing

Abstract: Summary Despite all technological advances, mapping cracks on concrete structures mostly remains to be evaluated through sketches based on on‐site observation and photographs. Methods based on image processing have been developed with clear advantages. However, most studies rely on perfectly identified areas or on single cracks without any other pathologies, being therefore unsuitable for on‐site application. In addition, the accuracy is not usually quantified due to the absence of ground‐truth. Thus, methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The importance close-range remote sensing and using multispectral cameras for damage assessment and crack detection on buildings was emphasized by numerous researchers [45][46][47]. In the last few years, a growing number of studies have shown the great potential of hyperspectral cameras for detection and mapping cracks on buildings [48,49]. Unmanned aerial vehicles (UAV) can be used for i.e., disaster management [50,51], crack identification using image processing [47,52], seismic vulnerability [53], architectural assessment of heritage sites and structures [54], and structural assessment using image processing techniques [55].…”
Section: The Assessment Methods For Condition Inspection and Identifimentioning
confidence: 99%
“…The importance close-range remote sensing and using multispectral cameras for damage assessment and crack detection on buildings was emphasized by numerous researchers [45][46][47]. In the last few years, a growing number of studies have shown the great potential of hyperspectral cameras for detection and mapping cracks on buildings [48,49]. Unmanned aerial vehicles (UAV) can be used for i.e., disaster management [50,51], crack identification using image processing [47,52], seismic vulnerability [53], architectural assessment of heritage sites and structures [54], and structural assessment using image processing techniques [55].…”
Section: The Assessment Methods For Condition Inspection and Identifimentioning
confidence: 99%
“…Indexing technology has been successfully applied to most relational database systems. Unlike other types of databases, multimedia databases need to adopt multidimensional indexing technology [9]. For aircraft landing gear images, multidimensional indexing is performed on multiple attributes of the image, and one index structure is used to retrieve multiple attributes, which can greatly shorten the response time.…”
Section: Spatial Index Structure Of Multimedia Databasementioning
confidence: 99%
“…Kim and Cho studied the automated vision‐based detection of cracks on concrete surfaces using a deep learning technique, 19 and Dunga explored the autonomous concrete crack detection using deep fully CNN, but pre‐training on ImageNet, migrating to the crack data set for secondary training is detrimental 20 . Santos et al carried out research on automatic mapping of cracking patterns on concrete surfaces with biological stains using hyperspectral images processing 21 . In recent years, with the increasing number of hyperparameters, especially when multiple layers are present, design architectures have become increasingly difficult.…”
Section: Introductionmentioning
confidence: 99%